ANALISIS EKONOMI PADA PERKUATAN RUMAH GUNA PENGURANGAN DAMPAK GEMPA BUMI - Mohamad F.N. Aulady; Felicia T. Nuciferani; Dyan Eka Nurhayati; Adi A. Pratama (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2021)
Indonesia berada pada